Integrated multidimensional process improvement methodology - Chan, Kok Keong. (2008)
Global competition, changing customers' needs, increasing product complexity, volatile economic conditions and higher customer expectation are the changing set of business requirements that causes the need for optimising productivity, improving quality and reducing cost. However, there is no scientific and methodical approach to address the productivity, quality and cost problems in an integrated and a unified manner. In this thesis, an Integrated Multidimensional Process Improvement Methodology (IMPIM) is developed to solve the yield management, process control and cost management problem. The enabling technologies for IMPIM are management concepts, information technology, artificial intelligence techniques and mathematical models. This thesis also formulates a step by step implementation of IMPIM.